1996
DOI: 10.1111/j.1600-0765.1996.tb00489.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of streptozotocin‐induced diabetes on neurogenic inflammation of gingivmucosal tissue in rat

Abstract: It has been suggested that the unmyelinated small diameter afferent nociceptive C-fibres are impaired in diabetes mellitus. We have recently demonstrated that these fibres are the prerequisite for neurogenic inflammation induced by mechanical or chemical irritations. These experiments were designed to characterize the neurogenic inflammatory responses of gingivomucosal tissue in the early phase of experimental induced diabetes mellitus in rat. Effect of dental ligature on the gingivomucosal (GM) vascular perme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…The effect of NGF on the neurogenic inflammatory response has not been, to our knowledge, previously investigated; although a reduced neurogenic response in the diabetic rat was first reported by Garcia‐Leme et al (1974) after stimulation of the saphenous nerve and confirmed in a related study (Gamse & Jansćo, 1985). A reduction of neurogenic inflammation has also been recently shown in the gingivomucosal tissue in the rat (Györfi et al , 1996). The conclusion from the study of Gamse & Jancsó (1985) was that the loss of the neurogenic response was a consequence of microvascular changes, rather than neuropeptide depletion.…”
Section: Discussionmentioning
confidence: 81%
“…The effect of NGF on the neurogenic inflammatory response has not been, to our knowledge, previously investigated; although a reduced neurogenic response in the diabetic rat was first reported by Garcia‐Leme et al (1974) after stimulation of the saphenous nerve and confirmed in a related study (Gamse & Jansćo, 1985). A reduction of neurogenic inflammation has also been recently shown in the gingivomucosal tissue in the rat (Györfi et al , 1996). The conclusion from the study of Gamse & Jancsó (1985) was that the loss of the neurogenic response was a consequence of microvascular changes, rather than neuropeptide depletion.…”
Section: Discussionmentioning
confidence: 81%
“…There are several animal studies that have examined the relationship between stress and periodontal disease. 56,[63][64][65][66][67][68] In an early study, Gupta et al 64 observed that the alveolar crest of the interradicular area in a stressed hamster showed areas of osteoclastic activity and a reduction in remodeling activity. As mentioned above, Breivik et al 55 demonstrated that the periodontal degradation enhanced in Fischer 344 rats that responded to high HPA axis reactivity after subcutaneous corticosterone delivery.…”
Section: Number Of Rats With Beaded Nerve Terminals At Sacrificementioning
confidence: 99%
“…Furthermore, it should be an important factor in the altered immune response that occurs in diabetes 33 . Other authors suggest that even the inflammatory responses induced by mechanical (dental ligature) and/or chemical irritants (topical application of capsaicin) in the gingivomucosal tissue are altered in streptozotocin‐diabetic rats, and this alteration at least partially results from the diabetes‐induced damage to the unmyelinated C fibers 34 . The regulation of the mucosal homeostasis seems even more complicated because the close anatomic associations suggest communication between nerve fibers and immune cells 35 …”
Section: Discussionmentioning
confidence: 99%
“…33 Other authors suggest that even the inflammatory responses induced by mechanical (dental ligature) and/or chemical irritants (topical application of capsaicin) in the gingivomucosal tissue are altered in streptozotocin-diabetic rats, and this alteration at least partially results from the diabetes-induced damage to the unmyelinated C fibers. 34 The regulation of the mucosal homeostasis seems even more complicated because the close anatomic associations suggest communication between nerve fibers and immune cells. 35 According to the results with experimental diabetes, it appears that not only does the number of mast cells increase significantly on the ground of diabetes in gingiva but the VEGFR2 expression of these mast cells rises as well.…”
Section: Discussionmentioning
confidence: 99%